The Oxford handbook of talent management - Collings, David G.,; Mellahi, Kamel,; Cascio, Wayne F., (Oxford handbooks online., 2017)
Draws upon perspectives from, inter alia, human resource management, psychology, and strategy to chart the topography of the area of talent management and to establish the base of knowledge in the field of talen management.